Variability of RUSLE Factor K in grasslands from high mountain environment (Sierra de las Nieves, southern Spain). - Martínez-Murillo, Juan Francisco; Menjíbar-Romero, Mario (My University, 2024)
United Nations declared the majority of world’s soil resources are in only fair, poor or very poor condition from soil degradation, so soil erosion is a major threat to soil. Mainly, this is the result of accelerated soil erosion processes as consequences of deforestation, overgrazing, tillage and unsuitable agricultural practices. Impacts can be severe, not only through land degradation and fertility loss, but through a conspicuous number of off-site effects leading to desertification. In one Mediterranean high mountain environment (Sierra de las Nieves, southern Spain), this study deals with the calculation of the RUSLE Factor K in grassland soils with different degrees of degradation due to grazing and water erosion. Also, Factor K is determined for badland materials as final stage of grassland degradation. To do this, soil surface conditions is described in three different types of grassland: nondegraded, semi-degraded, and degraded, besides in badland surface material. 10-soil samples from 0-10 cm of depth are taken in all of them to analysis in laboratory: bulk density, texture, organic matter content, permeability, and aggregate stability fraction. Finally, the Factor K is calculated based on the soil data. The results show a declining trend and significant differences between the sampled grassland and badland material: non-degraded 0.36±0.14, semi-degraded 0.56±0.13, degraded 0.68±0.12, and badland material 0.74±0.05. These significant differences are not achieved regarding mean aggregate stability fraction: nondegraded 28.7±10.5%, semi-degraded 35.8±7.9%, degraded 30.3±8.6%, and badland material 26.6±9.0%. Although the non-degraded grassland shows one Factor K indicating very low soil erodibility compared to the others and badland material, the aggregate stability data highlights a very fragile environment. Thus, when grassland is impacted by an increment in grazing activity and/or water erosion, it may become easily degraded. These results are key to...
Keywords: Suelos - Degradación; Erosión; Parque Nacional Sierra de las Nieves; Soil degradation; RUSLE Factor K; Grassland; Badland; High Mountain